ANALYSIS MODEL ALTMAN Z-SCORE DALAM MEMPREDIKSI GOING CONCERN YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2012 - 2016 - Wawan Saputra (LPPM POLITEKNIK LP3I BANDUNG, 2018)
This study aims determine the company’s financial performance that will be used to predict the possibility of going concern at a company. Research using bankruptcy prediction models Altman (Z-Score). This research is descriptive quantitative approach. In this method the financial statement is analyzed by using Z-Score variable which consists four ratios used are working capital to total assets, retained earnings to total assets, earnings before interest and tax to total assets and book value of equity to book value of debt. The research population was insurance companies listing of Indonesia Stock Exchange (BEI). The sample used in the research were twelve insurance companies are always listed on the Indonesia Stock Exchange (BEI) in year 2012-2016. The results of a research of twelve insurance companies listed on the stock exchange showed that three insurance companies are predicted to doubtful of going concern. Of the four variable used to predict doubtful of going concern, working capital to total assets (X1) variable that influence the going concern